Depictions of Socio-Cultural Elements in the Anime Series Attack On Titan Through Content Analysis Method - Faradilla, Nada; Ahmad, Hafiz Aziz (Universitas Muhammadiyah Malang, 2023)
Attack On Titan (進撃の巨人), adapted from the shonen manga series written and illustrated by Hajime Isayama, was chosen as the subject of study due to its weighty themes and visually appealing presentation. Several elements of this anime touch upon socio-cultural conditions in the real world, allowing viewers to resonate with the fictional world of Attack On Titan. Moreover, its depiction of graphic violence and implementation of social phenomena such as war and politics, provoke controversy among its audience. The purpose of this research is to analyze the visualization and frequency of socio-cultural themes in the anime Attack On Titan, as well as to formulate an understanding of its relevance to the representation of socio-cultural conditions and issues both in Japan and the world. This qualitative descriptive research employs content analysis as the method to analyze the socio-cultural elements present in Attack On Titan and their frequency of appearance. The research utilizes Mayring's Step Model of Inductive Category Development, employing an inductive approach to identify and categorize the socio-cultural elements within the anime. The research findings show that Attack On Titan uses symbolism to effectively represent Japanese culture and socio-cultural conditions. This adds novelty and depth to the animation while conveying the creator's intentions and cultural themes. Attack On Titan (進撃の巨人), diadaptasi dari seri manga shonen yang ditulis dan diilustrasikan oleh Hajime Isayama, dipilih sebagai subjek penelitian karena temanya yang berbobot dan presentasi yang menarik secara visual. Beberapa elemen anime ini menyentuh kondisi sosial budaya di dunia nyata, memungkinkan penonton untuk beresonansi dengan dunia fiksi Attack On Titan. Selain itu, penggambaran kekerasan grafis dan implementasi fenomena sosial seperti perang dan politik dalam anime tersebut menimbulkan kontroversi di kalangan penontonnya. Tujuan dari penelitian ini adalah menganalisis visualisasi dan frekuensi kemunculan tema sosiokultural dalam anime Attack On Titan, serta merumuskan pemahaman tentang relevansinya terhadap representasi kondisi dan isu sosiokultural baik di Jepang maupun di dunia. Penelitian deskriptif kualitatif ini menggunakan analisis isi sebagai metode untuk menganalisis unsur-unsur sosial budaya yang ada dalam Attack On Titan dan frekuensi kemunculannya. Penelitian ini menggunakan Model Langkah Pengembangan Kategori Induktif Mayring, menggunakan pendekatan induktif untuk mengidentifikasi dan mengkategorikan unsur-unsur sosial-budaya dalam anime. Temuan penelitian menunjukkan bahwa Attack On Titan menggunakan simbolisme untuk secara efektif mewakili budaya Jepang dan kondisi sosial budaya. Ini menambah kebaruan dan kedalaman animasi sambil menyampaikan maksud pencipta dan tema budaya.